Resilient Intersection Management With Multi-Vehicle Collision Avoidance - Worrawichaipat, Phuriwat; Gerding, Enrico; Kaparias, Ioannis; Ramchurn, Sarvapali (Frontiers in Sustainable Cities, 2021)
In this paper, we propose a novel decentralised agent-based mechanism for road intersection management for connected autonomous vehicles. In our work we focus on road obstructions causing major traffic delays. In doing so, we propose the first decentralised mechanism able to maximise the overall vehicle throughput at intersections in the presence of obstructions. The distributed algorithm transfers most of the computational cost from the intersection manager to the driving agents, thereby improving scalability. Our realistic empirical experiments using SUMO show that, when an obstacle is located at the entrance or in the middle of the intersection, existing state of the art algorithms and traffic lights show a reduced throughput of 65-90% from the optimal point without obstructions while our mechanism can maintain the throughput up to 94-99%.